The Influence of Influencers, Digital Marketing, and Discounts on Purchase Decisions at Sidoarjo Dimsum Shops: Pengaruh Influencer, Digital Marketing, dan Potongan Harga Terhadap Keputusan Pembelian pada Kedai Dimsum Sidoarjo - Priyanti, Nur Laily Dwi; Astuti, Mudji (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to detect the influence of influencers, digital marketing, and price discounts on purchasing decisions at Kedai Dimsum Sidoarjo partially or simultaneously. This type of research is a descriptive quantitative research type. This research was conducted at Kedai Dimsum Sidoarjo, which is located on Jalan Sumorame Candi, Sidoarjo Regency. The population in this research are buyers at